Atomically thin binary V–V compound semiconductor: a first-principles study12. Issue 27 (23rd June 2016) - Yu, Weiyang; Niu, Chun-Yao; Zhu, Zhili; Wang, Xiangfu; Zhang, Wei-Bing
Abstract : Using first-principles calculations, we propose a class of unexplored binary V–V compound semiconductors with monolayer black phosphorene and blue phosphorene structures. Abstract : Finding novel 2D semiconductors is crucial to develop next-generation low-dimensional electronic devices. Using first-principles calculations, we propose a class of unexplored binary V–V compound semiconductors (PN, AsN, SbN, AsP, SbP and SbAs) with monolayer black phosphorene (α) and blue phosphorene (β) structures. Our phonon spectra and room-temperature molecular dynamics (MD) calculations indicate that all compounds are very stable. Moreover, most of compounds are found to present a moderate energy gap in the visible frequency range, which can be tuned gradually by in-plane strain. Especially, α-phase V–V compounds have a direct gap, while β-SbN, AsN, SbP, and SbAs may be promising candidates for 2D solar cell materials due to a wide gap separating acoustic and optical phonon modes. Furthermore, vertical heterostructures can be also built using lattice matched α(β)-SbN and phosphorene, and both vdW heterostructures are found to have intriguing direct band gaps. The present investigation not only broadens the scope of layered group V semiconductors but also provides an unprecedented route for the potential applications of 2D V–V families in optoelectronic and nanoelectronic semiconductor devices.